IMPACT OF STAR-VA INTERVENTION ACROSS BEHAVIORAL SUBTYPES OF DEMENTIA. (11th November 2018) - Jedele, J M; Curyto, K; Ludwin, B; Karel, M J
Abstract: STAR-VA is an interdisciplinary, patient-centered, behavioral intervention to help Veterans Affairs Community Living Center (CLC) care teams understand and manage behavior symptoms of dementia (BSD). Empirical support demonstrates distinct subtypes of BSD. While previous evaluations have demonstrated effectiveness, the impact of STAR-VA across behavior subtypes has been recently evaluated. From 2013 to 2017, 352 veterans participated in STAR-VA implementation and evaluation. Target behaviors included physically aggressive (PA; n=75), physically non-aggressive (PNA; n=72), verbally aggressive (VA; n=88), verbally non-aggressive (VNA; n=71), and behavior deficit (BD; n=46). Using a differences-in-differences analytic approach, STAR-VA impact was estimated from pre- to post-assessment by subtype. Results demonstrate: (1) lower odds of rejection of care (Minimum Data Set 3.0) for PA versus PNA, (2) less frequent total aggressive behavior for VA and PA versus BD, and (3) lower Rating Anxiety in Dementia scores for VA and VNA versus PNA. Implications for STAR-VA implementation will be discussed.